PARASITE INFESTATION ON OREOCHROMIS NILOTICUS (LINNAEUS, 1758) FROM SELECTED FISH FARMS IN CEBU, PHILIPPINES - Delan, Gloria; Rosales, Raamah C; Rica, Rachel Luz V; Corrales, Christine M; Ilano, Anthony S (Journal of Agriculture and Technology Management, 2015)
This study was conducted to determine parasite infestation on Oreochromis niloticus Linnaeus (1758) cultured in the selected fish farms in the province of Cebu, Philippines. A total of 20 fish samples were collected from the selected fresh and brackish water fish farms and dissected on the day of collection. Microscopic examination was conducted on 100 specimens comprising of liver, muscle, intestines, gills, skin and scales dissected from the fish samples. A total of 806 organisms were collected from these organs of the fish host. Allorganisms identified were classified under 14 genera. The 12 genera belong to parasitic groups dominated by protozoans of ciliates and flagellates such as Piscinoodinium, Trichodina, Cryptobia, Icthyophthirius, Chilodonella, andAmbiphrya. Organismsbelonging to other genera of parasitic groups were Dactylogyrus, Ergasilus,Myxozoa, Coccidia, Microsporidiaandalarval fluke. There were two other organisms classified as Navicula and Pleurosigma, but were not in the parasitic group. Higher diversity of parasites occurred in fish samples from freshwater farms than in brackish water environment. The species diversity of parasites could have been influenced by some environmental factors.